Fungsi leksikal "bunga" dalam simpulan bahasa dan peribahasa bahasa Melayu (Jurnal Bahasa, 2005)
Malay language has many ways in describing various things and events. Idiom is one of the very fine ways to say something which"make the Malay language unique and beautiful. Every word chosen in idiomatic phrases has its own aesthetical and lexical functions. Different from the common words used in daily communication, the words chosen in idiomatic phrases are very much related to the way of thinking among the Malay people, who always refer to their surrounding world as a symbolic way of telling something. The word "bunga" does not only carry its own lexical meaning, but also reveal the creativity of Malay traditional people in applying the concept of "bunga" with people's behaviours or attitudes, things, matters and events revolved around their life. This paper will discuss about the lexical functions of the word "bunga" used in Malay idiomatic phrases.